(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Children are at low risk of severe coronavirus infection. However, it is unclear whether symptoms persist in this age group, and long-term symptoms of COVID-19 can negatively affect the physical and mental development of children. Objective: to identify and predict changes in the hemostasis system during the recovery period in children with coronavirus infection.